2008
DOI: 10.1213/ane.0b013e3181865733
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Cyclooxygenase-1 Inhibition Before Coronary Artery Surgery: Aggregometry Versus Patient Self-Reporting

Abstract: Our results suggest that arachidonic acid-induced aggregation in whole blood may be a better predictor of platelet-related coagulopathy and platelet transfusion than the assessment of aspirin intake by patient self-reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…In addition, comparison studies showed only poor agreement between different methods for analyzing platelet function [13,34]. Although the usefulness of questionnaires for aspirin compliance and predicting bleeding during cardiac surgery has been reported [35], such self-reporting may not be fully reliable [6]. However, non-compliance of some patients would not explain changes in the test results before and after PTS transport and, therefore, does not question the study results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, comparison studies showed only poor agreement between different methods for analyzing platelet function [13,34]. Although the usefulness of questionnaires for aspirin compliance and predicting bleeding during cardiac surgery has been reported [35], such self-reporting may not be fully reliable [6]. However, non-compliance of some patients would not explain changes in the test results before and after PTS transport and, therefore, does not question the study results.…”
Section: Discussionmentioning
confidence: 99%
“…Impedance aggregometry was performed on a Multiplate TM analyzer (Dynabite) according to the manufacturer's instructions. This system has been previously described in detail [6,7,13,14]. Briefly, it measures increases in impedance between electrodes caused by platelet aggregation.…”
Section: Impedance Platelet Aggregometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The test has also been found to be able to detect impaired hemostasis after CPB surgery [35][36][37] and to identify patients before and after cardiac surgery with enhanced risk of bleeding and of blood transfusion 38,39 .…”
Section: The Influence Of Omega-3 Pufas In Cpb Procedures On the Activmentioning
confidence: 99%
“…In the past five years, MEA has become an important and widely used diagnostic tool for coagulation monitoring with respect to hereditary [8] and acquired [7,[9][10][11][12][13] platelet dysfunction, as well as surveillance of platelet inhibitor effects [14][15][16][17][18][19], as shown by many studies. Taking less than 10 minutes, MEA allows conclusions to be drawn about the patient's platelet function from standardized test procedures that are easy to perform.…”
Section: Introductionmentioning
confidence: 99%